„Cartea românească de învăţătură” a mitropolitului Varlaam al Moldovei. Izvoarele şi originalitatea - Dan Zamfirescu (Revista de Istorie și Teorie Literară)
The paper summarizes the author monograph „Cartea românească de învăţătură” a mitropolitului Varlaam (Bucharest, 2013, 1100 p.) dedicated to the Metropolitan of Moldavia Varlaam’s Romanian Book of Learning, also known as Homiliary (1643), in which answers are given to problems that have not been solved in the past century: Which were the sources the author worked with? How did he write it and wherein lies its originality? What is its value in the history of Post-Byzantine Orthodox preaching and of Romanian literature and theology?